Perancangan Aplikasi Inventory Berbasis Web pada General Steel Supplier Menggunakan Metode Extreme Programming: - - Agustina Andriani; Johanes Fernandes Andry (Fakultas Ilmu Komputer, Universitas Klabat, 2023)
The usage of information technology has grown fast in many sectors of human life. An information technology system that has an important impact on the development of the company's business is required. The inventory system is one of the systems that play an important role to ensure the company's success. General Steel Supplier is a steel company that has a process of collecting goods data and controlling goods in the warehouse that is irregular and highly susceptible to human error. Companies like General Steel Supplier frequently face inventory issues where there is a mismatch in the amount of inventory between the records created and the physical stock in the warehouse, causing a stock difference. The purpose of this research is to create a proposed web-based inventory application for General Steel Suppliers that may be used as a guide for improving inventory management performance. The Extreme Programming method is used in inventory application development, and it consists of Planning, Design, Coding, and Testing. This research developed a web-based inventory application that is used to help all parties involved in managing inventory data in the warehouse, including inventory, incoming goods, outgoing goods, goods returns, and printing reports.